Model Organisasi Ideal Bagi Perguruan Tinggi Islam di Indonesia - Afiful Ikhwan (Tarbiyah Departement collaboration with AMCA, 2014)
One organizational model control system determining the many Islamic university. Organizational model at the core of managerial work to develop a theory of management. An organization said to be ideal if an appropriate portion of the division of labor, hierarchy of authority clear, high formalization, Impersonal, making appropriate competent subordinates and careers. Organizational model that is too follow the formalities, will be hampered his pace. The model of an ideal organization for Islamic Universities in Indonesia is Unbiropatologi Organic models and its leader are transformational.